What do we know about nutrient-based strategies targeting molecular mechanisms associated with obesity-related fatty liver disease? - Ingrid Rivera-Iñiguez; Arturo Panduro; Sonia Roman; Karina González-Aldaco (Annals of Hepatology, 2023)
Obesity is a risk factor for developing nonalcoholic fatty liver disease (NAFLD), and the associated molecular mechanisms could be targeted with nutrient-based strategies. Therefore, it is necessary to review the current mechanisms to propose further treatments. Obesity facilitates the onset of insulin resistance, lipidic abnormalities, hepatic fat accumulation, lipid peroxidation, mitochondrial dysfunction, excessive reactive oxygen species (ROS) production, and inflammation, all related to further steatosis progression and fibrosis. Microbiota alterations can also influence liver disease by the translocation of pathogenic bacteria, energy extraction from short chain fatty acids (SCFAs), intestinal suppression of the expression of fasting-induced adipose factor (FIAF), reduction of bile acids, and altered choline metabolism. There are also genetic polymorphisms in metabolic proteins that predispose to a higher risk of liver diseases, such as those found in the patatin-like phospholipase domain-containing 3 (PNPLA3), transmembrane 6 superfamily member 2 (TM6SF2), membrane-bound O-acyltransferase domain-containing 7 (MBOAT7) or also known as lysophosphatidylinositol acyltransferase 1 (LPIAT1), transmembrane channel-like 4 genes (TMC4), fat mass and obesity-associated protein (FTO), the b Klotho (KLB) and carboxylesterase (CES1). No clear dietary guidelines target all mechanisms related to NAFLD development and progression. However, energy and carbohydrate intake restriction, regular physical exercise, supplementation of antioxidants, and restoration of gut microbiota seem to have beneficial effects on the new proposed features of NAFLD.